KUALITAS PELAYANAN KESEHATAN MASYARAKAT LANJUT USIA DI PUSKESMAS DUONO KECAMATAN IBU TABARU KABUPATEN HALMAHERA BARAT (JURNAL ADMINISTRASI PUBLIK, 2022)
This study aims to determine the Quality of Elderly Public Health Services at the Duono HealthCenter, Ibu Tabaru District, West Halmahera Regency. This type of research uses qualitativedescriptive. All data that have been presented are in accordance with primary and secondary data.Based on the results of the study according to the indicators, namely accuracy in service time,courtesy and friendliness when providing services, ease of getting service, and consumer comfort.But what happened at the Duono Health Center until now the quality of service has not been goingwell, this is indicated by the lack of facilities and infrastructure provided so that it is not in accordancewith the number of visits, besides that there are facilities and infrastructure that are poorly maintainedso that they do not provide comfort for the community/ elderly patients at the Duono Health Center,there are still service officers who provide services that are not according to the stated schedule. Thenumber of medical personnel at the Duono Health Center, in this case Doctors, Midwives, andNurses, is still lacking and not balanced. There are still employees or medical personnel who are noton time in providing health services, lack of friendliness in providing services and cannot providecomfort in providing services. Elderly public health services must be further improved so that theQuality of Elderly Public Health Services at the Duono Health Center is more effective.Keywords : Quality, Health Services, Elderly Society